BURNOUT SYNDROME AMONG DOCTORS AND NURSES/TECHNICIANS EMPLOYED IN THE GENERAL HOSPITAL OF THE HEALTH CENTER IN BRCKO - Nikolic, Aleksandra; Nikolic, Aleksandra; Grujicic, Sandra (HEALTH CARE, 2022)
Introduction/Aim: Burnout syndrome can be defined as a prolonged response to chronic emotional and interpersonal stressors associated with the workplace. It is usually manifested as emotional exhaustion, a feeling of reduced personal accomplishment and depersonalization. It most often occurs in people who work intensively with people, especially doctors, teachers, where even 20-30% of employees show some of the symptoms of burnout syndrome at work. The aim of the study is to evaluate the prevalence of burnout syndrome among healthcare workers (doctors and nurses/technicians) in the general hospital of the Health Center Brcko and to identify the predictors of emotional exhaustion, depersonalization and a feeling of reduced personal accomplishment.Methods: This cross-sectional study was conducted during June and July 2018, in the general hospital of the Health Center Brcko. The research included doctors (61) and nurses/technicians (155), aged 18 and older, who were employed full time. All respondents voluntarily agreed to participate anonymously in the research. The data were obtained from the respondents with the help of questionnaires. In addition to the general questionnaire, Maslach Burnout Inventory – Human Services Survey (MBI-HSS) was used to assess burnout syndrome at work. In the statistical analysis of data, the following methods of descriptive statistics were applied: mean value, standard deviation. T-test for independent samples, univariate and multivariate logistic regression analysis were used to compare the two groups of respondents. Variables that had p
Keywords: burnout syndrome, healthcare workers, cross-sectional study